2018
DOI: 10.1188/18.onf.496-507
|View full text |Cite
|
Sign up to set email alerts
|

Distress and Supportive Care Needs of Ethnically Diverse Older Adults With Advanced or Recurrent Cancer

Abstract: Nursing assessment of patient SCNs and distress is integral to establishing individualized patient-centered care plans and to delivering optimal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
1
7
0
1
Order By: Relevance
“…The presence of higher distress in younger patients (DT score ≥4) coincided with findings reported in the literature (Van Scheppingen et al, 2011;Goulia et al, 2012;Kim et al, 2013;Haynes-Lewis et al, 2018). In a study of adolescents and young adults in China (15-39 years), Xie et al ( 2017) reported a prevalence of 89.1% of DT score ≥4.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of higher distress in younger patients (DT score ≥4) coincided with findings reported in the literature (Van Scheppingen et al, 2011;Goulia et al, 2012;Kim et al, 2013;Haynes-Lewis et al, 2018). In a study of adolescents and young adults in China (15-39 years), Xie et al ( 2017) reported a prevalence of 89.1% of DT score ≥4.…”
Section: Discussionsupporting
confidence: 82%
“…In Haynes-Lewis et al ’s 14▪ study, fear of cancer spreading and concerns about the worries of close others were the most common unmet psychological needs reported by 52 and 44% of older patients with advanced cancer, respectively; while clinically significant distress was reported by 33% of the patients. The study further demonstrated that those older patients with clinically significant distress had greater likelihood to report multiple supportive care needs 14▪. Older patients with advanced cancer are also likely to experience significantly increased depressive symptoms when the disease comes to the terminal stage 34.…”
Section: Psychosocial and Spiritual Needsmentioning
confidence: 95%
“…If the information obtained is insufficient or confusing, older patients with advanced cancer would experience a sense of uncertainty regarding the disease prognosis and treatment outcomes, which can further aggravate their psychological distress 39. Older patients with increased distress tend to have higher needs for information 14▪ (Fig. 1).…”
Section: Information Needsmentioning
confidence: 99%
“…This framework has been used successfully in previous needs assessment studies with various types of cancer survivors, including PC (Fitch & Steele, 2010;Fitch, 2012). In this study, the SCFCC was used to guide the selection of validated instruments to measure unmet SC needs and informed the development of the qualitative interview guide (Cheah et al, 2016;Haynes-Lewis et al, 2018). Lastly, it guided the categorization and interpretation of the findings, identifying unmet SC needs across domains that were prevalent and had the potential to negatively impact the overall health and QOL of PC survivors living with advanced disease.…”
Section: Theoretical Frameworkmentioning
confidence: 99%